Australia : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2010)
Australia's statistics are of a high quality. Based on the review of its statistical practices, a set of recommendations is presented designed to increase its adherence to internationally accepted statistical practices. The aim of the review is to enhance the usefulness of Australia's statistics in terms of cross-cutting recommendations, making national accounts series available; a national consumer price index; producer price index; and government finance statistics to include a breakdown of stocks and flows of financial assets and liabilities, monetary statistics, balance of payments, and international investment position statistics.